The persistence of Theileria parva infection in cattle immunised using two stocks which differ in their ability to induce a carrier state: Analysis using a novel blood spot PCR assay - Skilton, Robert A.; Bishop, Richard P.; Katende, J.M.; Mwaura, S.; Morzaria, S.P. (2002)
An improved Theileria parva DNA detection assay based on the polymerase chain reaction (PCR) using primers derived from the 104 kDa antigen (p104) gene was developed to detect parasite DNA in blood spots on filter paper. The specificity of the assay was validated using DNA from a wide range of cattle-derived and buffalo-derived stocks of T. parva. DNA of T. annulata, T. buffeli, T. lestoquardi, T. mutans and T. taurotragi was not amplified using the p104 primers. The detection threshold of the assay was approximately 1-2 parasites/microl of infected blood. PCR amplification using the p104 primers was applied to sequential samples from groups of cattle experimentally infected with either the T. parva Marikebuni stock that induces a long-term carrier state or the Muguga stock, which does not induce a carrier state. The study extended for up to 487 days post-infection and PCR data from defined time points were compared with parasitological microscopy and serological data, together with xenodiagnosis by experimental application of ticks. Microscopy first detected piroplasms between days 13 and 16 after infection whereas all cattle became PCR +ve between days 9 and 13. Animals infected with the Muguga stock of T. parva had parasite DNA in the peripheral blood, which could be detected by PCR, for between 33 and 129 days post-infection in different animals. By contrast parasite DNA in the blood of cattle infected with the Marikebuni stock could be detected consistently from day 9 up to 487 days, when the study terminated. The data suggest that the nature and persistence of the carrier state may differ markedly between different T. parva parasite stocks.